Implementation of Deep Breathing Relaxation Techniques to Control Anger at Violent Behavior - Fitry, Amalia Pasca; Ramdani, Vikri Haikal; Suhanda, Suhanda; Rosmiati, Rosmiati (KIAN JOURNAL, 2023)
Objective: This case study was conducted to describe the application of deep breathing relaxation techniques to control anger in patients with violent behavior Method: The design of this research uses case studies through a qualitative approach that focuses on the application of nursing interventions. The participants used in this study were Mr. P is 32 years old, a man with a mental disorder with violent behavior. The process of assessment and diagnosis is focused on the main problem. Objective and subjective data become a reference for periodic evaluations of nursing implementation. The research location was carried out at the BLUD of Banjar City Hospital on 25-28 May 2022. Results: Based on the results of nursing care, signs and symptoms were obtained, namely the subjective data of the client being angry, annoyed and injuring himself while the objective data of the client looked annoyed, the face was red, the hands clenched and the client was silent. bow down in shame because of his actions. The nursing problem found is violent behavior. The intervention given is a deep breathing relaxation technique. Conclusion: The therapeutic intervention of deep breathing relaxation techniques has proven effective in controlling anger in patients with violent behavior and clients say that after the intervention they become calmer, relaxed and able to control angry feelings.